THE EFFECT OF THE STRATEGY OF IMAGINATION ON THE ACHIEVEMENT OF SECOND GRADERS IN SCIENCE SUBJECT - Prof. Dr. Ali Matani Ali Al-Anbaki; Nour Al-Huda Hussein Alwan Gomaa (Journals Park Publishing, 2022)
The research aims to identify the effect of the strategy of imagination in the achievement of second-grade students in the intermediate science subject, as the research sample included two groups, one of which was the experimental group and the number of its students was (40) students, and the other represented the control group and the number of its students was (36) students, and in the intentional way the researcher chose (Al-Hassan Bin Ali High School (PBUH)) from the research community represented by the middle schools affiliated to the Directorate of Education of Diyala Governorate / Baquba. The researcher adopted the experimental research method as a method for conducting her research, which includes one independent variable (imagination strategy) and a dependent variable (scholastic achievement). As the researcher chose the experimental design to control the research variables, and before starting to apply the experiment, the researcher rewarded the two research groups for the purpose of obtaining accurate results with the following variables: (chronological age calculated in months, students’ previous achievement, previous information test, Raven’s intelligence test). After making the equivalence between the two research groups, the researcher prepared the requirements of the application of plans, objectives and tests for the two research groups, and after completing the application of the experiment, the researcher applied her research tools to the two research groups, as the researcher obtained data for the two research groups, as these data were statistically processed by a test ( t-test) for two independent samples and the results are shown; The students of the experimental group outperformed the students of the control group who studied according to the (Imagination strategy) in the achievement of science subject.
Keywords: imagination strategy; academic achievement; second-intermediate students